Reflections on Schoen, the Greeks and Modern Man - Jackson, Basil (Journal of psychology and theology, 1976)
A response to Edward L. Schoen's “Aristotle's Modern Conception of Man: A Reply to Basil Jackson” (Journal of Psychology and Theology, 1975, 3, 109–115). Schoen's article was in reply to Jackson's “The Psuche in Psychology and Theology” (Journal of Psychology and Theology, 1975, 3, 3–10).